Weaving care inter-relational and empowerment - Rosalini, Maria Helena Perreira (2017)
This study develops an intervention in a community with a training job of network of care. The focus on the theme “empowerment” began a project whose proposal is to work with the techniques of “Caring for the Caregiver,” with a group director of an institution in a community in a situation of social vulnerability. The group offers food and education, professional and religious, through activities socio-educational and cultural, aiming to raise awareness of social rights, autonomy and empowerment of people. There is an appreciation of the care practice with the possibility of emancipation. The team has already held a practice of valuing the knowledge existing in the community and is open to learning about the empowerment of people. The proposal aims to develop learning strategies with the team through the active participation of the people, to construct meaning and intervention in the community. This intervention is part of an Research-Action. Based on the knowledge of the group, using the concepts of active learning methodology and social participation of Paulo Freire is to trigger the dialogue process, the concepts of “Art of Caring” and “Experiences of Care” proposed by Adalberto Barreto. It has built a learning since 2010 which is scheduled to extend into the community in 2013, is being evaluated by analysis from focus groups, which occur in the process, and the community will be measured by questionnaires in 2014 and socioeconomic validated and the instrument quality of life WHOQOL of the world Health Organization.